The Relationship Between Social Interaction and Elderly Happiness in A Social Center for The Elderly - Desi Puspita Sari; Suryati Suryati; Emi Puspita Dewi (Grief and Trauma, 2025)
This study is entitled The Relationship between Social Interaction and Happiness of the Elderly at the Harapan Kita Palembang Social Home for the Elderly. The background of this study explains that the elderly often face various problems such as decreased physical abilities and health, and a lack of attention from those closest to them, so that social interaction becomes very important for their well-being and happiness. The study will focus on the relationship between social interaction and happiness of the elderly at the Harapan Kita Palembang Social Home for the Elderly. Good social interaction can help the elderly feel useful, healthy, and get support from their surroundings. The formulation of the problem in this study is how the Relationship between Social Interaction and Happiness of the Elderly at the Harapan Kita Palembang Social Home for the Elderly. The research method used is a type of quantitative research using a correlational approach, data collection techniques using questionnaires, interviews, and documentation. The results of the study showed that social interaction has a significant influence on the level of happiness of the elderly. The analysis shows a strong positive correlation between social interaction and happiness of the elderly, with a determination coefficient of 56%, while the remaining 44% is influenced by other factors not studied. This shows that social interaction routines can have a positive impact on the elderly in overcoming problems involving happiness, such as getting closer to each other, providing inner peace, and maturing thinking to face problems. Thus, it can be concluded that social interaction plays an important role in improving the quality of life of the elderly in the shelter.